Analisa Sampel Komposite dengan Menggunakan XRF Metode Fuse Bead untuk Mengurangi Pemakaian Flux pada Analisa Nikel Ore - Irawati Ramli; Nurhikmah Wahab; Rizka Octavia; Alfiah Indriastuti; Riki Kusumah (Akademi Teknologi Industri Dewantara Palopo, 2024)
Composite analysis in a geological or mining context, especially for nickel ore, the theoretical basis refers to the concept of sampling and mineral processing. Composite sampling is carried out to obtain an accurate representation of a mineral deposit. Composite samples involve combining several individual samples to represent the overall properties of a material. The importance of composite data in processing mineral reserve information. Composite samples are used to smooth out fluctuations in mineral content and allow a better estimate of the average value of mineral content in the deposit. The implementation stage of this research consists of a small number of samples from several parts (a, c, d) being mixed into one combined sample, which is then analyzed to produce results that represent the average of all samples, by taking 0.25 grams of each sample to reach a total of 1 gram, then analyze the combined results. And using an X-Ray Fluorescence (XRF) tool with the Fuse Bead method. From the results of the research conducted by the author, a conclusion was obtained that it met the acceptance requirements. The accuracy rate obtained was 99.21%. which has a low error rate of 0.79%. The use of flux in the composite stage is more profitable, in terms of the efficiency of adding flux and the efficiency of working on samples compared to using the usual stage which still uses the process of processing samples one by one with the addition of more flux from the composite stage.